Inflammation Markers and Major Depressive Disorder in Patients With Chronic Heart Failure. Issue 7 (September 2015) - Xiong, Glen L.; Prybol, Kevin; Boyle, Stephen H.; Hall, Russell; Streilein, Robert D.; Steffens, David C.; Krishnan, Ranga; Rogers, Joseph G.; O'Connor, Christopher M.; Jiang, Wei
ABSTRACT Background Major depressive disorder (MDD) and chronic heart failure (CHF) have in common heightening states of inflammation, manifested by elevated inflammation markers such as C-reactive protein. This study compared inflammatory biomarker profiles in patients with CHF and MDD to those without MDD. Methods The study recruited patients admitted to inpatient care for acute heart failure exacerbations, after psychiatric diagnostic interview. Patients with Beck Depression Inventory (BDI) scores lower than 10 and with no history of depression served as the nondepressed reference group (n = 25). MDD severity was defined as follows: mild (BDI 10-15; n = 48), moderate (BDI 16–23; n = 51), and severe (BDI ≥ 24; n = 33). A Bio-Plex assay measured 18 inflammation markers. Ordinal logistic models were used to examine the association of MDD severity and biomarker levels. Results Adjusting for age, sex, statin use, body mass index, left ventricular ejection fraction, tobacco use, and New York Heart Association class, the MDD overall group variable was significantly associated with elevated interleukin (IL)-2 (p = .019), IL-4 (p = .020), IL-6 (p = .026), interferon-γ (p = .010), monocyte chemoattractant protein 1 (p = .002), macrophage inflammatory protein 1β (p = .003), and tumor necrosis factor α (p = .004). MDD severity subgroups had a greater probability of elevated IL-6, IL-8, interferon-γ, monocyte chemoattractant protein 1, macrophage inflammatory protein 1β, and tumor necrosis factor α compared with nondepressed group. The nondepressed group had greater probability of elevated IL-17 (p < .001) and IL-1β (p < .01). Conclusions MDD in patients with CHF was associated with altered inflammation marker levels compared with patients with CHF who had no depression. Whether effective depression treatment will normalize the altered inflammation marker levels requires further study. Trial Registration: ClinicalTrials.gov NCT00078286.